Život a dílo Jeana Sibelia - Vacek, Kristian (Akademie múzických umění v Praze. Hudební fakulta AMU. Knihovna, 2010)
Life and work of Jean Sibelius describing hii most valuable writings in a factographical way and also his important life period-